ANALISIS MICROTHEACHING DALAM MENINGKATKAN KETERAMPILAN MENGAJAR MAHASISWA PRODI PENDIDIKAN BAHASA JERMAN UNIVERSITAS NEGERI MEDAN - Habeahan, Deviana Claudia; Saruksuk, Wiwik Maywan; Sitorus, Dinda Oktaveresia; Simbolon, Gita Febriyanti; Nainggolan, Katlin Febrina; Simamora, Christy Aprilia; Sihombing, Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of micro-teaching on improving teaching skills of German Language Education Study Program students at Medan State University. The problem identified is the need to improve students teaching skills before plunging into the real world of education. This research used descriptive qualitative method with research subjects of 20-25 students who had taken the micro-teaching course. Data were collected through participatory observation, in-depth interviews, documentation, and questionnaires. Data analysis used thematic analysis which included data reduction, data grouping, and data interpretation with data triangulation for validity. The results showed that micro-teaching contributed positively to the development of basic teaching skills, especially in the ability to speak and interact with students (69.9%), the use of teaching methods (46.4%), and classroom management (28.6%). However, mastery of the material (25%) still needs to be improved. This study concludes that micro-teaching is effective in improving students' teaching skills, but there needs to be optimization in the aspects of mastery of material and classroom management.